The effect of leader-member exchange (LMX) on the relationship between motivating language (ML) dimensions and management effectiveness of Waqf properties by Waqf institutions in Malaysia - Sharfizie Mohd Sharip (Tanjong Malim, 2020)
The effect of leader-member exchange (LMX) on the relationship between motivating language (ML) dimensions and management effectiveness of Waqf properties by Waqf institutions in Malaysia by Sharfizie Mohd Sharip